2023
DOI: 10.1371/journal.pone.0280689
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and wellbeing of further and higher education students returning to face-to-face learning after Covid-19 restrictions

Abstract: Aim This study aimed to examine the mental health and wellbeing of further and higher education students and the associating factors after returning to face-to-face (in-person) learning after Covid-19 restrictions. Methods A cross-sectional study informed by student consultations was conducted using a survey design. Mental health and wellbeing were assessed using self-report items on the Depression, Anxiety and Stress Scale (DASS-21) and the Short Warwick–Edinburgh Mental Wellbeing Scale (SWEMWBS). Descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…At the same time, it highlighted the opportunities offered by online educational materials in distance education, providing information that cultivates critical thinking [39]. This confirms that although students may be able to return to face-to-face education, they are likely to continue to face mental health and well-being challenges related to the pandemicstress may persist for some students as PTSD (49.4 %), as mentioned in a recent study in Australia [25,33].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…At the same time, it highlighted the opportunities offered by online educational materials in distance education, providing information that cultivates critical thinking [39]. This confirms that although students may be able to return to face-to-face education, they are likely to continue to face mental health and well-being challenges related to the pandemicstress may persist for some students as PTSD (49.4 %), as mentioned in a recent study in Australia [25,33].…”
Section: Discussionsupporting
confidence: 55%
“…On the other hand, previous research has shown that the wider use of distance education after the end of the Covid-19 pandemic, provided an opportunity to create new contexts of interaction through the development of innovative digital technologies (67% of participants) [24]. Meanwhile, another study found a strong link between negative emotions and the use of communication technologies, as they isolate people and deprive them of interaction [25]. However, one of the elements that needs immediate attention in the education system is the provision of mental health services and the implementation of studentcentred methods and practices that focus on the prevention and restoration of mental health and wellbeing.…”
Section: Discussionmentioning
confidence: 95%
“…These proportions were quite similar to Greek students. Another cross-sectional study on December 2021 and June 2022 reported moderate anxiety and depression, associated with gender, age, and studies [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted an international survey between December 2021 and July 2022 that aimed to examine the mental health and wellbeing of further and higher education students returning to face-to-face (in-person) learning after the COVID-19 pandemic restrictions were lifted [46]. Owing to the aims of the current study, a sample of that dataset was deemed appropriate, since several studies highlighted that the COVID-19 pandemic was a stressful period for students [46][47][48][49]. The total sample from the original dataset consisted of N = 1160 post-secondary students recruited internationally from a variety of education settings, including colleges and universities [46].…”
Section: Data Source and Preparationmentioning
confidence: 99%